AMBIVALENCE IN MOHAMMED KAMICI EL-HASSANI’S LE MOUCHOIR - Ida Bagus Putra Ananta Sidhiswara (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
The present study discusses the ambivalent behavior found in the character(s) in a francophone novel written by a third world writer. This ambivalence is represented by the attitude of the East that is against the colonialists on the one hand, but admires them and imitates their identities and attitudes on the other. This ambivalent discourse is widely represented in a francophone work entitled Le Mouchoir (1987) by Mohamed Kacimi El-Hassani. This novel satirically tells about Algeria in the post-colonial period and the narrator’s efforts to oppose colonialism. Textual citations and pieces of evidence from the novel that are used to support the analysis are those that are related to postcolonial and ambivalence issues. The analysis is also supported by historical evidence of French colonialists’ behavior towards indigenous Maghreb. The interpretation of the findings is supported by Homi Bhabha's ambivalence theory. Moreover, this study was conducted using Fairclough's critical discourse analysis methodology with which the textual analysis of the novel follows three levels of discourse, namely micro, meso, and macro levels. This study found that the hypocritical nature of the characters such as that demonstrated by the narrator and Mahfoud reflects the postcolonial nature of